Effect of environmental temperature on semen quality and seminal plasma metabolites of Mediterranean buffalo bulls. Issue 5 (3rd October 2022) - Sun, Le; Cui, Zhichao; Huang, Shihai; Xue, Qingsong; Rehman, Saif ur; Luo, Xi; Shi, Deshun; Li, Xiangping
Abstract: High-quality semen with high viability is critical to improving the in-vitro fertilization efficiency. This study aimed to understand the effect of ambient temperature and humidity on semen quality and seminal plasma biochemical parameters of Mediterranean buffalo in March and July. The metabolites of seminal plasma in two seasons were detected using the UPLC-MS/MS method. The results showed that temperature and humidity index (THI) in March were 66.86 ± 2.98, and 82.94 ± 3.52 in July. Compared with in March, breath frequency, rectal temperature, and heat shock protein 70 expressions of seminal plasma were significantly increased in July ( p <  0.05), motility of sperm was dramatically reduced, and sperm deformity rate was significantly increased ( p <  0.05). Fructose, acid phosphatase and α-glucosidase in seminal plasma were significantly increased ( p <  0.05) in July, while testosterone level was significantly reduced ( p <  0.05). Six different metabolites were found in the two groups, which involved in three metabolic pathways, the tricarboxylic acid cycle, glycerophospholipid, glyoxylic acid and dicarboxylic acid. The above results indicate that the increased ambient temperature has obvious side effects on the semen quality of Mediterranean buffalo, and the compromised quality is associated with the change of metabolites related to male hormone secretion, energy metabolism and fatty acid oxidation.